Numerical analysis of the influence of the last cycle scheme on plasticity induced crack closure - Camas, D. (2019)
Plasticity induced crack closure is considered the main mechanism related to the premature contact of the crack flanks when a crack grows under cyclic loadings. This phenomenon has been studied numerically since the early 70s, when some researchers approached to metal fatigue problems by means of the finite element analysis. The numerical analysis requires the development of a plastic wake. How this plastic wake is developed has influence on the crack closure results and a great impact on the computational cost. When running a finite element analysis, it is not possible to consider all the loading cycles involved in an experimental test. The numerical effort is not acceptable. Therefore, in this work, the crack growth scheme is analyzed. In particular, the influence of the number of loading cycles after releasing the last set of nodes on plasticity induced crack closure results is studied. A CT aluminum specimen has been modelled three-dimensionally and several simulations have been run to evaluate the influence of the loading cycles after releasing the last set of nodes. The numerical analysis is made in terms of crack closure and opening values.